A matrigel-free method for culture of pancreatic endocrine-like cells in defined protein-based hydrogels - Kozlowski, Mark T.; Zook, Heather N.; Chigumba, Desnor N.; Johnstone, Christopher P.; Caldera, Luis F.; Shih, Hung-Ping; Tirrell, David A.; Ku, Hsun Teresa (Frontiers in Bioengineering and Biotechnology, 2023)
The transplantation of pancreatic endocrine islet cells from cadaveric donors is a promising treatment for type 1 diabetes (T1D), which is a chronic autoimmune disease that affects approximately 9 million people worldwide. However, the demand for donor islets outstrips supply. This problem could be solved by differentiating stem and progenitor cells to islet cells. However, many current culture methods used to coax stem and progenitor cells to differentiate into pancreatic endocrine islet cells require Matrigel, a matrix composed of many extracellular matrix (ECM) proteins secreted from a mouse sarcoma cell line. The undefined nature of Matrigel makes it difficult to determine which factors drive stem and progenitor cell differentiation and maturation. Additionally, it is difficult to control the mechanical properties of Matrigel without altering its chemical composition. To address these shortcomings of Matrigel, we engineered defined recombinant proteins roughly 41 kDa in size, which contain cell-binding ECM peptides derived from fibronectin (ELYAVTGRGDSPASSAPIA) or laminin alpha 3 (PPFLMLLKGSTR). The engineered proteins form hydrogels through association of terminal leucine zipper domains derived from rat cartilage oligomeric matrix protein. The zipper domains flank elastin-like polypeptides whose lower critical solution temperature (LCST) behavior enables protein purification through thermal cycling. Rheological measurements show that a 2% w/v gel of the engineered proteins display material behavior comparable to a Matrigel/methylcellulose-based culture system previously reported by our group to support the growth of pancreatic ductal progenitor cells. We tested whether our protein hydrogels in 3D culture could derive endocrine and endocrine progenitor cells from dissociated pancreatic cells of young (1-week-old) mice. We found that both protein hydrogels favored growth of endocrine and endocrine progenitor cells, in contrast to Matrigel-based culture. Because the protein hydrogels described here can be further tuned with respect to mechanical and chemical properties, they provide new tools for mechanistic study of endocrine cell differentiation and maturation.